Synthesis of New Phosphine-Containing Hg Complexes Derived from 2-Thiouracil and Evaluation of Their Biological Activity - Lubna Waleed Mohammed; Sabah Farhan Mohammed; Maha Mohammed Sulaiman; Mohammed Jwher Saleh; Jamil Nadhem Saleh; Marwan Hasan Ali (Physical Sciences, Life Science and Engineering, 2025)
The study involved the formation of several new mercury complexes by reacting 2-thiouracil with mercury chloride and sodium hydroxide to yield the mercury complex L1. This reaction was considered the basis for preparing other complexes, as it reacts with two moles of triphenylphosphine (PPh3) to form complex L2, and through the reaction of complex L1 with bis(diphenylphosphanyl)methane (dppm) to create complex L3, and with 1,2-bis(diphenylphosphanyl)ethane (dppe) to form complex L4, and with 1,3-bis(diphenylphosphanyl)propane (dppp) to form complex L5. The validity of the prepared complexes was confirmed through spectral measurements, including the infrared spectrum and the proton and phosphorus nuclear magnetic resonance spectra. The presence of new bands in the infrared spectrum, such as the (Hg-N) and (Hg-O) bands, provided evidence of a bond. Mercury with thiouracil as between the bands belonging to (P-Ph) and (C-P), proof of the association of phosphine with the metal, and between the 1H-NMR spectrum, there are signals belonging to the benzene ring in phosphine, and this was confirmed by their complements, which were identical to the protons of the benzene rings. Between the 31P-NMR spectrum, there is a single signal indicating that the association is double in phosphine with the presence of one isomer of the complexes. The effectiveness of the prepared complexes was tested on two types of bacteria, positive and negative, using the antibiotic amoxicillin as a control sample. The confounders showed a direct relationship with the concentration, and the L2 complex showed the highest effectiveness against the two types of bacteria studied.